Fiber aqueous zinc ion battery based on gel zinc powder negative electrode and preparation method of fiber aqueous zinc ion battery
By adopting gel zinc powder negative electrode and winding structure design in fiber water-based zinc ion batteries, the problem of poor stability and difficulty in continuous construction of zinc negative electrode is solved, and a fiber water-based zinc ion battery with high stability and long cycle life is achieved.
Patent Information
- Application Number
- CN202411878907.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The problem of poor stability of zinc negative electrodes of fiber-based zinc ion batteries is difficult to construct continuously.
The gel zinc powder negative electrode is used, and the positive and negative electrode current collectors of the fiber battery are coated with zinc powder slurry and the gel zinc powder electrode is polymerized as the fiber negative electrode, and a manganese dioxide positive electrode and cellulose separator are combined to form a wound structure battery.
The stability of the negative electrode of the fiber-water zinc ion battery is significantly improved, the continuous construction of the battery and high cycle life are achieved, and the stable cycle can be more than 450 hours at the surface current density of 1mA/cm2 and the surface capacity of 1mAh/cm2.
Smart Images

Figure CN119852556A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flexible fiber batteries, and specifically relates to a fiber aqueous zinc ion battery and a preparation method thereof. Background Art
[0002] In recent years, the rise of portable and wearable electronic devices has strongly promoted the development of green and highly safe flexible energy storage power sources. Among them, flexible fiber batteries have received special attention due to their advantages such as miniature, flexibility and integration with traditional fabrics. Traditional fiber lithium-ion batteries have safety hazards such as high toxicity and easy combustion and explosion due to the use of organic electrolytes. Fiber aqueous zinc-ion batteries with metallic zinc as the negative electrode have lower redox reaction potential (-0.76V vsSHE), higher theoretical specific capacity (820mAh / g or 5855mAh / cm 3 ) and outstanding intrinsic safety, it is considered to be a highly promising next-generation flexible energy storage device. At present, the construction of fiber aqueous zinc-ion batteries is mainly achieved by using zinc wire as the negative electrode to match the fiber positive electrode with a lower active material loading. However, zinc wire as both the fiber current collector and the negative electrode active material also brings a series of problems: on the one hand, the use of zinc wire reduces the flexibility of the fiber battery. During the repeated bending and cyclic charge and discharge of the battery, the zinc wire is prone to fatigue fracture, resulting in battery performance degradation or even failure; on the other hand, the zinc wire negative electrode will lead to a higher negative / positive electrode capacity ratio (N / P ratio), thereby reducing the energy density of the entire fiber battery device.
[0003] Compared with the integrated fiber form of traditional zinc wire, granular zinc powder has the advantages of low cost, good processability, and strong adjustability. It can be made into electrode slurry by adjusting the surface area to be compatible with the continuous coating and preparation process of existing fiber batteries. However, the different failure mechanisms caused by the different appearance of zinc powder compared with zinc wire limit its practical application. The larger contact area between zinc powder and electrolyte increases its corrosion risk and worsens the inherent thermodynamic instability of zinc in aqueous electrolyte, thereby promoting water reduction to generate hydrogen and changing the local pH value near the electrode. The strong alkaline environment formed will further corrode the zinc surface and lead to zinc loss and the formation of byproducts such as zinc hydroxide / zinc oxide, which ultimately limits the electrochemical performance and service life of fiber aqueous zinc ion batteries. Limiting the direct contact between the zinc anode and the free water in the electrolyte can significantly improve the thermodynamic stability of the zinc anode. Although some previous studies have improved the stability of the zinc anode in aqueous electrolytes by constructing organic / inorganic coatings on the surface of zinc metal foil, this simple coating strategy is very easy to cause the coating to rupture due to the volume expansion / contraction of the fiber during the large-capacity deposition / stripping process of the fiber zinc anode, which ultimately leads to battery failure. At present, there are few reports on the protection of fiber zinc powder anodes and the construction strategies of fiber aqueous zinc ion full batteries. Therefore, it is urgent to develop an effective protection strategy for high-stability zinc powder anodes and a continuous construction method for fiber aqueous zinc ion batteries. Summary of the invention
[0004] In view of the problems of poor stability of the zinc negative electrode of the fiber aqueous zinc ion battery and difficulty in continuous construction, the object of the present invention is to provide a fiber aqueous zinc ion battery based on a gel zinc powder negative electrode with high stability and continuous construction, and a preparation method thereof.
[0005] The fiber aqueous zinc ion battery based on gel zinc powder negative electrode provided by the present invention uses nickel and copper wire as positive and negative electrode current collectors of the fiber battery respectively, and zinc powder slurry is coated on the current collector and gel zinc powder electrode is polymerized in situ as the fiber negative electrode, and manganese dioxide slurry is coated on the current collector as the fiber positive electrode; a cellulose diaphragm is wrapped around the surface of the fiber manganese dioxide positive electrode and twisted with the fiber gel zinc powder negative electrode to prepare a wound structure fiber aqueous zinc ion battery; the integrated organic gel zinc powder negative electrode and the aqueous electrolyte form a two-phase interface through phase separation, thereby avoiding the occurrence of side reactions such as hydrogen evolution and corrosion caused by the intrinsic thermodynamic instability of zinc powder in the aqueous electrolyte, thereby effectively improving the stability of the fiber aqueous zinc ion battery negative electrode; the specific preparation steps include: preparation of organic gel precursor solution, preparation of electrode slurry, preparation of fiber gel zinc powder negative electrode, preparation of fiber manganese dioxide positive electrode and assembly of fiber zinc ion full battery.
[0006] The preparation method of the fiber aqueous zinc ion battery based on the gel zinc powder negative electrode provided by the present invention comprises the following specific steps:
[0007] (1) Preparation of organogel precursor solution: The organogel precursor solution is prepared by ultrasonic dissolution. First, a certain amount of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) is added to the organic solvent of tri(2,2,2-trifluoroethyl) phosphate (TFEP), and the solution is placed in an ultrasonic cleaner to completely dissolve the zinc salt; then, polyethylene glycol dimethacrylate (PEGDMA) monomer is added to the obtained organic electrolyte solution and stirred until the solution is uniform and transparent; then, 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) is added as a photoinitiator for ultraviolet polymerization, and finally, the obtained organogel precursor solution is wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring;
[0008] (2) Preparation of electrode slurry: For zinc powder electrode slurry, first weigh a certain amount of polyvinylidene fluoride (PVDF) powder, add it to N-methylpyrrolidone (NMP) solvent, stir it to completely dissolve it, and obtain a binder solution; then weigh a certain amount of zinc powder, multi-walled carbon nanotube powder and tin powder respectively, put them into a mortar, mix and grind them, then add them to the above binder solution, stir continuously to mix evenly, and obtain zinc powder electrode slurry; for manganese dioxide electrode slurry, first weigh a certain amount of polyvinylidene fluoride (PVDF) powder, add it to N-methylpyrrolidone (NMP) solvent, stir it to completely dissolve it, and obtain a binder solution; then weigh a certain amount of manganese dioxide powder and conductive carbon black respectively, put them into a mortar, grind them, and then add them to the above binder solution, stir continuously to mix evenly, and obtain manganese dioxide electrode slurry.
[0009] (3) Preparation of fiber gel zinc powder negative electrode: The prepared zinc powder negative electrode slurry is loaded into the slurry cylinder, and the motor is turned on to make the customized copper wire fiber current collector pass through the slurry cylinder filled with zinc powder negative electrode slurry at a uniform speed, and then pass through the temperature gradient hot air drying tube and then be wound and rolled to obtain the fiber zinc powder negative electrode; further, in a vacuum glove box, the obtained fiber zinc powder electrode is soaked in organic gel precursor solution and passed through an ultraviolet light irradiation device, and after in-situ photo-initiated free radical polymerization, it is rolled up to obtain the fiber gel zinc powder negative electrode.
[0010] (4) Preparation of fibrous manganese dioxide positive electrode: The prepared manganese dioxide electrode slurry is loaded into the slurry barrel, and the motor is turned on to make the customized nickel wire fiber current collector pass through the barrel filled with manganese dioxide slurry at a uniform speed, and then pass through a temperature gradient hot blast drying tube and then be wound and rolled to obtain a fibrous manganese dioxide positive electrode.
[0011] (5) Assembly of fiber aqueous zinc ion full battery: First, the obtained fiber manganese dioxide positive electrode is wrapped around a cellulose diaphragm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber zinc ion battery cell with a wound structure. The cell is packaged using a commercial FEP tube and injected with bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte. The tabs are led out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
[0012] Furthermore, the specific preparation process of the organogel precursor solution in step (1) is as follows: first, 1.56-12.5 grams of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt is added to 5-10 milliliters of tri(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution is placed in an ultrasonic cleaner for ultrasonication for 50-120 minutes until the zinc salt is completely dissolved to obtain a 0.5-2 mol / L organic electrolyte solution; then, 1-5 grams of polyethylene glycol dimethacrylate (PEGDMA) monomer is added to the above solution and magnetically stirred for 10-30 minutes until the solution is uniform and transparent; then, 3wt%-8wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) is added as a photoinitiator for ultraviolet polymerization, and finally, the obtained organogel precursor solution is wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring for 30-60 minutes.
[0013] Furthermore, the specific preparation process of the electrode slurry in step (2) is as follows: in order to prepare a zinc powder electrode slurry with a solid content of 40wt%-43wt%, firstly, 6wt%-10wt% of polyvinylidene fluoride (PVDF) powder in the solid is weighed and added to 5-10 ml of N-methylpyrrolidone (NMP) solvent and stirred for 5-10 hours to completely dissolve it, then 70wt%-80wt% of zinc powder, 8wt%-12wt% of multi-walled carbon nanotube powder and 5wt%-10wt% of tin powder in the solid are weighed and mixed in a mortar and ground for 20-40 minutes, and then added to the above-mentioned binder solution and stirred continuously for 12-24 hours. hours, and after uniform mixing, zinc powder electrode slurry is obtained; for manganese dioxide electrode slurry with a solid content of 16wt%-20wt%, firstly weigh 8wt%-12wt% of polyvinylidene fluoride (PVDF) powder in the solid, add it to 5-10 ml of N-methylpyrrolidone (NMP) solvent and stir for 5-10 hours to completely dissolve it, then weigh 65wt%-75wt% of manganese dioxide powder and 15wt%-25wt% of conductive carbon black in the solid respectively, put them into a mortar, mix and grind for 20-40 minutes, then add them to the above-mentioned binder solution, stir continuously for 12-24 hours, and after uniform mixing, obtain manganese dioxide electrode slurry.
[0014] Furthermore, the specific preparation process of the fiber gel zinc powder negative electrode in step (3) is as follows: the prepared zinc powder slurry is loaded into a slurry barrel, the motor is started to make the customized copper wire fiber current collector pass through the barrel containing the zinc powder slurry at a uniform speed of 2-6 revolutions per minute, and then passed through a temperature gradient hot blast drying tube (the drying temperatures of the front, middle and rear sections are 170-190 degrees Celsius, 130-150 degrees Celsius and 90-110 degrees Celsius respectively) and then wound and rolled to obtain a fiber zinc powder negative electrode, and then the obtained fiber zinc powder electrode is soaked in an organic gel precursor solution in a vacuum glove box and irradiated by an ultraviolet light irradiation device for 1-3 minutes, and after in-situ photoinitiated free radical polymerization, it is rolled up to obtain a fiber gel zinc powder negative electrode.
[0015] Furthermore, the specific preparation process of the fiber manganese dioxide positive electrode in step (4) is as follows: the prepared manganese dioxide electrode slurry is loaded into the slurry barrel, the motor is started to make the customized nickel wire fiber current collector pass through the barrel filled with manganese dioxide slurry at a uniform speed of 2-6 revolutions per minute, and then pass through a temperature gradient hot air drying tube (the drying temperatures of the front, middle and rear sections are 130-150 degrees Celsius, 90-110 degrees Celsius and 50-70 degrees Celsius respectively) and then wind and roll to obtain the fiber manganese dioxide positive electrode.
[0016] Furthermore, the specific assembly process of the fiber aqueous zinc ion full battery in step (5) is as follows: first, the fiber manganese dioxide positive electrode is wound around a cellulose diaphragm with a width of 2-4 mm by a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode by a twisting device to obtain a fiber zinc ion battery cell with a wound structure, which is packaged using commercial FEP tubing and injected with a 0.5-2 mol / L bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte, the pole ears are led out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
[0017] The fiber aqueous zinc ion battery based on the gel zinc powder negative electrode obtained by the above preparation method has a simple structure and is easy to assemble, and has the advantages of high stability and continuous preparation.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The fiber gel zinc powder negative electrode prepared by the present invention has the characteristics of high stability and long cycle life compared with the traditional zinc powder negative electrode. 2 The surface current density and 1mAh / cm 2 The surface capacity can be stably cycled for more than 450 hours.
[0020] (2) The present invention prepares a fiber gel zinc powder negative electrode by developing a confined coating method and an in-situ polymerization strategy, providing a universal strategy for continuously constructing a high-stability fiber zinc powder negative electrode, effectively overcoming the challenges faced by traditional fiber zinc metal wires and zinc powder negative electrodes, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the process for preparing fiber gel zinc powder anode by confined coating method and in situ polymerization strategy.
[0022] Figure 2 Optical and scanning electron microscope photos of the continuously prepared fiber gel zinc powder negative electrode.
[0023] Figure 3 Cyclic voltammetry curve of zinc / / copper half-cell based on gel zinc powder negative electrode and constant current charge-discharge curve at current density of 0.2 A / g.
[0024] Figure 4 Schematic diagram of the in-situ polymerization preparation of fiber gel zinc powder negative electrode and the change in contact angle of the electrode at different times of infiltration of the precursor solution.
[0025] Figure 5 This is the voltage-time curve of the zinc / / zinc symmetric battery based on gel zinc powder negative electrode during the long-term cycle test and the constant current charge and discharge curve at a current density of 1A / g.
[0026] Figure 6 It is a structural schematic diagram, a real picture of the battery cell and a scanning electron microscope picture of an aqueous zinc-ion battery based on gel zinc powder negative electrode fiber.
[0027] Figure 7 It is the Coulomb efficiency cycle curve of the fiber zinc / / copper half-cell based on the gel zinc powder negative electrode and the constant current charge and discharge curve of the corresponding aqueous zinc ion full battery at a current density of 0.5A / g. DETAILED DESCRIPTION
[0028] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
[0029] The reagents used in the following examples were all purchased from outside, such as zinc powder (≥99.9%), N-methylpyrrolidone (NMP, electronic grade, 99.99%), polyethylene glycol dimethacrylate (PEGDMA, M w ≈1000) were purchased from Aladdin.
[0030] Multi-walled carbon nanotubes (MWCNT, ≥95%, particle size 8-15 nm, length ≈50 nm, specific surface area>140m 2 / g), tin powder (particle size 500 nm, purity 99.99%), zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2, purity 98%), and 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP, purity 98%+) were purchased from Adamas.
[0031] Tris(2,2,2-trifluoroethyl) phosphate (TFEP) was purchased from Duoduo Chemical Reagents.
[0032] Manganese dioxide nanorods (α phase) were purchased from Future Materials Technology Co., Ltd.
[0033] Polyvinylidene fluoride (PVDF, HSV900) was purchased from Dongguan Zhanyang Polymer Materials Co., Ltd.
[0034] Embodiment 1, a preparation method of a fiber aqueous zinc ion battery based on a gel zinc powder negative electrode, the specific steps are:
[0035] (1) Preparation of organogel precursor solution: First, 3.13 g of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt was added to 5 ml (7.82 g) of tris(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution was ultrasonically cleaned for 60 minutes until the zinc salt was completely dissolved to obtain a 1 mol organic electrolyte solution; then, 5 g of polyethylene glycol dimethacrylate (PEGDMA) monomer was added to the above solution and magnetically stirred for 30 minutes until the solution was uniform and transparent; then, 5 wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) was added as a photoinitiator for ultraviolet polymerization, and finally, the obtained organogel precursor solution was wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring for 40 minutes.
[0036] (2) Preparation of electrode slurry: In order to prepare a zinc powder electrode slurry with a solid content of 41 wt%, firstly, 8 wt% (0.286 g) of polyvinylidene fluoride (PVDF) powder in the slurry was weighed and added to 5 ml (5.14 g) of N-methylpyrrolidone (NMP) solvent, and stirred for 6 hours to completely dissolve it; then, 75 wt% (2.68 g) of zinc powder, 10 wt% (0.36 g) of multi-walled carbon nanotube powder and 7 wt% (0.25 g) of tin powder in the solid were weighed and mixed in a mortar and ground for 30 minutes, and then added to the above-mentioned binder solution, and stirred continuously for 24 hours until it was uniformly dissolved. After mixing, zinc powder electrode slurry is obtained; for manganese dioxide electrode slurry with a solid content of 18wt%, first weigh 10wt% (0.113g) of polyvinylidene fluoride (PVDF) powder in the solid, add it to 5ml (5.14g) of N-methylpyrrolidone (NMP) solvent and stir for 6 hours to completely dissolve it, then weigh 70wt% (0.791g) of manganese dioxide powder and 20wt% (0.226g) of conductive carbon black in the solid into a mortar, mix and grind for 30 minutes, then add it to the above-mentioned binder solution, stir continuously for 24 hours, and obtain manganese dioxide electrode slurry after uniform mixing.
[0037] (3) Preparation of fiber gel zinc powder negative electrode: The prepared zinc powder slurry is loaded into the slurry barrel, and the motor is turned on to make the customized composite copper wire fiber current collector pass through the barrel containing the zinc powder slurry at a uniform speed of 4 revolutions per minute. Then, it passes through a temperature gradient hot blast drying tube (the drying temperatures of the front, middle and rear sections are 180 degrees Celsius, 140 degrees Celsius and 100 degrees Celsius, respectively) and is wound and rolled to obtain a fiber zinc powder negative electrode. Then, the obtained fiber zinc powder electrode is soaked in an organic gel precursor solution in a vacuum glove box and irradiated by an ultraviolet light irradiation device for 1 minute. After in-situ photoinitiated free radical polymerization, it is rolled up to obtain a fiber gel zinc powder negative electrode.
[0038] (4) Preparation of fibrous manganese dioxide positive electrode: The prepared manganese dioxide electrode slurry is loaded into a slurry barrel, and the motor is turned on to make the customized composite nickel wire fiber current collector pass through the barrel containing the manganese dioxide slurry at a uniform speed of 4 revolutions per minute. Then, it passes through a temperature gradient hot air drying tube (the drying temperatures of the front, middle and rear sections are 140 degrees Celsius, 100 degrees Celsius and 60 degrees Celsius, respectively) and is then wound and rolled to obtain a fibrous manganese dioxide positive electrode.
[0039] (5) Assembly of fiber aqueous zinc ion full battery: First, the fiber manganese dioxide positive electrode is wound around a cellulose diaphragm with a width of 3 mm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber zinc ion battery cell with a wound structure. The cell is packaged using commercial FEP tubing and injected with 1 mol / L bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte. The tabs are drawn out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
[0040] In this embodiment, the schematic diagram of the preparation process of coating zinc powder slurry and in-situ polymerization to prepare a fiber gel zinc powder negative electrode is as follows: Figure 1 As shown; the optical and scanning electron microscope photos of the fiber gel zinc powder negative electrode prepared continuously are shown Figure 2 as shown; Figure 3 As shown, the cyclic voltammograms of the zinc / / copper half-cell based on the gel zinc powder negative electrode at a scan rate of 1 mV / s highly overlap in the first 7 cycles, showing excellent cycle stability. The assembled fiber gel zinc powder / / manganese dioxide full cell has a high discharge specific capacity of 254.8 mAh / g at a current density of 0.2 A / g.
[0041] Example 2, a method for preparing a fiber aqueous zinc ion battery based on a gel zinc powder negative electrode, the specific steps are:
[0042] (1) Preparation of organogel precursor solution: First, 2.5 g of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt was added to 8 ml (12.5 g) of tris(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution was ultrasonically cleaned for 50 minutes until the zinc salt was completely dissolved to obtain a 0.5 mol organic electrolyte solution; then, 4 g of polyethylene glycol dimethacrylate (PEGDMA) monomer was added to the above solution and magnetically stirred for 20 minutes until the solution was uniform and transparent; then, 4 wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) was added as a photoinitiator for ultraviolet polymerization, and finally, the obtained organogel precursor solution was wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring for 50 minutes.
[0043] (2) Preparation of electrode slurry: In order to prepare a zinc powder electrode slurry with a solid content of 42 wt%, firstly, 7 wt% (0.52 g) of polyvinylidene fluoride (PVDF) powder in the solid was weighed and added to 10 ml (10.28 g) of N-methylpyrrolidone (NMP) solvent and stirred for 5 hours to completely dissolve it. Then, 73 wt% (5.43 g) of zinc powder, 12 wt% (0.89 g) of multi-walled carbon nanotube powder and 8 wt% (0.6 g) of tin powder in the solid were weighed and mixed in a mortar and ground for 20 minutes. Then, the mixture was added to the above-mentioned binder solution and stirred for 18 hours. After uniform mixing, zinc powder electrode slurry is obtained; for manganese dioxide electrode slurry with a solid content of 17wt%, first weigh 8wt% (0.17g) of polyvinylidene fluoride (PVDF) powder in the solid, add it to 10ml (10.28g) of N-methylpyrrolidone (NMP) solvent and stir for 5 hours to completely dissolve it, then weigh 75wt% (1.58g) of manganese dioxide powder and 7wt% (0.15g) of conductive carbon black in the solid respectively into a mortar, mix and grind for 20 minutes, then add it to the above-mentioned binder solution, stir continuously for 18 hours, and obtain manganese dioxide electrode slurry after uniform mixing.
[0044] (3) Preparation of fiber gel zinc powder negative electrode: The prepared zinc powder slurry is loaded into the slurry barrel, and the motor is turned on to make the customized composite copper wire fiber current collector pass through the barrel containing the zinc powder slurry at a uniform speed of 3 revolutions per minute. Then, it passes through a temperature gradient hot blast drying tube (the drying temperatures of the front, middle and rear sections are 170 degrees Celsius, 130 degrees Celsius and 90 degrees Celsius, respectively) and is wound and rolled to obtain a fiber zinc powder negative electrode. Then, the obtained fiber zinc powder electrode is soaked in an organic gel precursor solution in a vacuum glove box and irradiated by an ultraviolet light irradiation device for 2 minutes. After in-situ photoinitiated free radical polymerization, it is rolled up to obtain a fiber gel zinc powder negative electrode.
[0045] (4) Preparation of fibrous manganese dioxide positive electrode: The prepared manganese dioxide electrode slurry is loaded into the slurry barrel, and the motor is turned on to make the customized composite nickel wire fiber current collector pass through the barrel containing the manganese dioxide slurry at a uniform speed of 3 revolutions per minute. Then, it passes through a temperature gradient hot air drying tube (the drying temperatures of the front, middle and rear sections are 130 degrees Celsius, 90 degrees Celsius and 50 degrees Celsius, respectively) and is then wound and rolled to obtain a fibrous manganese dioxide positive electrode.
[0046] (5) Assembly of fiber aqueous zinc ion full battery: First, the fiber manganese dioxide positive electrode is wound around a cellulose diaphragm with a width of 2 mm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber zinc ion battery cell with a wound structure. The cell is packaged using commercial FEP tubing and injected with 0.5 mol / L bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte. The tabs are drawn out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
[0047] In this embodiment, during the preparation of the fiber gel zinc powder negative electrode, the organic gel precursor solution can quickly infiltrate the zinc powder electrode and undergo free radical polymerization in situ under ultraviolet light irradiation to form a gel. The schematic diagram of the in situ polymerization mechanism and the schematic diagram of the contact angle change of the precursor solution infiltrating the electrode at different times are shown in FIG. Figure 4 The prepared gel zinc powder negative electrode has excellent electrochemical stability, as shown in Figure 5 As shown, the Zn / / Zn symmetric battery based on gel zinc powder anode is 2 The surface current density and 1mAh / cm 2 During the long-term cycle test at a surface capacity of 1.54 W, the overpotential remained stable even after 450 hours of deposition / stripping; the assembled fiber gel zinc powder / / manganese dioxide full battery had a discharge specific capacity of 165.5 mAh / g at a current density of 1 A / g.
[0048] Example 3, a method for preparing a fiber aqueous zinc ion battery based on a gel zinc powder negative electrode, the specific steps are:
[0049] (1) Preparation of organogel precursor solution: First, 9.38 g of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt was added to 10 ml (15.64 g) of tris(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution was ultrasonically cleaned for 120 min until the zinc salt was completely dissolved to obtain a 1.5 mol organic electrolyte solution; then, 3 g of polyethylene glycol dimethacrylate (PEGDMA) monomer was added to the above solution and magnetically stirred for 25 min until the solution was uniform and transparent; then, 7 wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) was added as a photoinitiator for ultraviolet polymerization, and finally, the obtained organogel precursor solution was wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring for 30 min.
[0050] (2) Preparation of electrode slurry: In order to prepare a zinc powder electrode slurry with a solid content of 40 wt%, firstly, 6 wt% (0.33 g) of polyvinylidene fluoride (PVDF) powder in the solid was weighed and added to 8 ml (8.22 g) of N-methylpyrrolidone (NMP) solvent and stirred for 7 hours to completely dissolve it. Then, 80 wt% (4.38 g) of zinc powder, 8 wt% (0.44 g) of multi-walled carbon nanotube powder and 6 wt% (0.33 g) of tin powder in the solid were weighed and mixed in a mortar and ground for 25 minutes. Then, the mixture was added to the above-mentioned binder solution and stirred for 12 hours until it was uniformly dissolved. After mixing, zinc powder electrode slurry is obtained; for manganese dioxide electrode slurry with a solid content of 19wt%, first weigh 8wt% (0.15g) of polyvinylidene fluoride (PVDF) powder in the solid, add it to 8ml (8.22g) of N-methylpyrrolidone (NMP) solvent and stir for 7 hours to completely dissolve it, then weigh 67wt% (1.29g) of manganese dioxide powder and 25wt% (0.48g) of conductive carbon black in the solid into a mortar, mix and grind for 25 minutes, then add it to the above-mentioned binder solution, stir continuously for 12 hours, and obtain manganese dioxide electrode slurry after uniform mixing.
[0051] (3) Preparation of fiber gel zinc powder negative electrode: The prepared zinc powder slurry is loaded into the slurry barrel, and the motor is turned on to make the customized composite copper wire fiber current collector pass through the barrel containing the zinc powder slurry at a uniform speed of 5 revolutions per minute. Then, it passes through a temperature gradient hot blast drying tube (the drying temperatures of the front, middle and rear sections are 190 degrees Celsius, 150 degrees Celsius and 110 degrees Celsius, respectively) and is wound and rolled to obtain a fiber zinc powder negative electrode. Then, the obtained fiber zinc powder electrode is soaked in an organic gel precursor solution in a vacuum glove box and irradiated by an ultraviolet light irradiation device for 3 minutes. After in-situ photoinitiated free radical polymerization, it is rolled up to obtain a fiber gel zinc powder negative electrode.
[0052] (4) Preparation of fibrous manganese dioxide positive electrode: The prepared manganese dioxide electrode slurry is loaded into the slurry barrel, and the motor is turned on to make the customized composite nickel wire fiber current collector pass through the barrel containing the manganese dioxide slurry at a uniform speed of 5 revolutions per minute. Then, it passes through a temperature gradient hot air drying tube (the drying temperatures of the front, middle and rear sections are 150 degrees Celsius, 110 degrees Celsius and 70 degrees Celsius, respectively) and is then wound and rolled to obtain a fibrous manganese dioxide positive electrode.
[0053] (5) Assembly of fiber aqueous zinc ion full battery: First, the fiber manganese dioxide positive electrode is wound around a cellulose diaphragm with a width of 4 mm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber zinc ion battery cell with a wound structure. The cell is packaged using commercial FEP tubing and injected with 1.5 mol / L bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte. The tabs are drawn out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
[0054] In this embodiment, the fiber aqueous zinc ion battery based on the gel zinc powder negative electrode is a twisted winding structure, and its corresponding structural schematic diagram, battery cell physical diagram and scanning electron microscope diagram are shown in the figure. Figure 6 As shown. The fiber aqueous zinc ion battery based on gel zinc powder negative electrode at 1mA / cm 2 and 1mAh / cm 2 Under the test conditions, it can stably cycle 300 times. The discharge capacity of the assembled fiber gel zinc powder / / manganese dioxide full battery at a current density of 0.5A / g is 207.3mAh / g. The corresponding coulombic efficiency cycle curve and constant current charge and discharge curve are shown in Figure 7 shown.
Claims
1. A fiber aqueous zinc ion battery based on a gel zinc powder negative electrode, characterized in that: Nickel and copper wire are used as positive and negative current collectors of the fiber battery respectively, zinc powder slurry is coated on the current collector and gel zinc powder electrode is in-situ polymerized as a fiber negative electrode, and manganese dioxide slurry is coated on the current collector as a fiber positive electrode; a cellulose diaphragm is wrapped around the surface of the fiber manganese dioxide positive electrode and twisted with the fiber gel zinc powder negative electrode to prepare a wound structure fiber aqueous zinc ion battery; a two-phase interface is formed between the integrated organic gel zinc powder negative electrode and the aqueous electrolyte through phase separation, thereby avoiding the occurrence of side reactions such as hydrogen evolution and corrosion caused by the intrinsic thermodynamic instability of zinc powder in the aqueous electrolyte, thereby effectively improving the stability of the fiber aqueous zinc ion battery negative electrode.
2. A method for preparing a fiber aqueous zinc ion battery based on a gel zinc powder negative electrode, characterized in that: The specific steps are: (1) Preparation of organogel precursor solution: The organogel precursor solution is prepared by ultrasonic dissolution. First, zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt is added to 5-10 ml of tri(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution is placed in an ultrasonic cleaner to completely dissolve the zinc salt. Then, polyethylene glycol dimethacrylate (PEGDMA) monomer is added to the obtained organic electrolyte solution, and the solution is stirred until the solution is uniform and transparent. Then, 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) is added as a photoinitiator for ultraviolet polymerization. Finally, the obtained organogel precursor solution is wrapped with aluminum foil to block light and placed on a magnetic stirring table for stirring. (2) Preparation of electrode slurry: For zinc powder electrode slurry, first, polyvinylidene fluoride (PVDF) powder is added to N-methylpyrrolidone (NMP) solvent and magnetically stirred to completely dissolve it to obtain a binder solution; then, zinc powder, multi-walled carbon nanotube powder and tin powder are mixed and ground in a mortar, and then added to the above binder solution, and continuously stirred to mix evenly to obtain zinc powder electrode slurry; For manganese dioxide electrode slurry, first, a certain amount of polyvinylidene fluoride (PVDF) powder is weighed and added to N-methylpyrrolidone (NMP) solvent, and stirred to completely dissolve it to obtain a binder solution; then, a certain amount of manganese dioxide powder and conductive carbon black are weighed, ground and mixed in a mortar, and then added to the above binder solution, and continuously stirred to obtain manganese dioxide electrode slurry; (3) Preparation of fiber gel zinc powder negative electrode: the prepared zinc powder slurry is loaded into the slurry cylinder, and the motor is turned on to make the customized copper wire fiber current collector pass through the cylinder filled with zinc powder slurry at a uniform speed, and then pass through the temperature gradient hot blast drying tube and then wind and roll to obtain the fiber zinc powder negative electrode; in the glove box, the obtained fiber zinc powder electrode is soaked in the organic gel precursor solution and then passed through the ultraviolet light irradiation device, and after in-situ light-induced free radical polymerization, it is rolled up to obtain the fiber gel zinc powder negative electrode; (4) Preparation of fiber manganese dioxide positive electrode: The prepared manganese dioxide electrode slurry is loaded into the slurry barrel, and the motor is turned on to make the customized nickel wire fiber current collector pass through the barrel filled with manganese dioxide slurry at a uniform speed, and then pass through the temperature gradient hot blast drying tube and then wind and roll to obtain the fiber manganese dioxide positive electrode; (5) Assembly of fiber aqueous zinc ion full battery: First, the obtained fiber manganese dioxide positive electrode is wrapped around a cellulose diaphragm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber aqueous zinc ion battery cell with a wound structure, which is then packaged with a FEP tube and injected with bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte, and the pole ears are led out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
3. The preparation method according to claim 2, characterized in that: The specific preparation process of the organogel precursor solution in step (1) is as follows: first, 1.56-12.5 grams of zinc bis(trifluoromethanesulfonyl)imide (Zn(TFSI)2) electrolyte salt is added to 5-10 milliliters of tris(2,2,2-trifluoroethyl) phosphate (TFEP) organic solvent, and the solution is placed in an ultrasonic cleaner for ultrasonication for 50-120 minutes until the zinc salt is completely dissolved to obtain a 0.5-2 mol / L organic electrolyte solution; then, 1-5 grams of polyethylene glycol dimethacrylate (PEGDMA) monomer is added to the above solution and magnetically stirred for 10-30 minutes until the solution is uniform and transparent; then, 3wt%-8wt% of 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) is added as a photoinitiator for ultraviolet polymerization; finally, the obtained organogel precursor solution is wrapped with aluminum foil to block light and placed on a magnetic stirring table for uniform stirring for 30-60 minutes.
4. The preparation method according to claim 2, characterized in that: The specific preparation process of the electrode slurry in step (2) is as follows: prepare a zinc powder electrode slurry with a solid content of 40wt%-43wt%, first weigh 6wt%-10wt% of polyvinylidene fluoride (PVDF) powder in the solid, add it to 5-10 ml of N-methylpyrrolidone (NMP) solvent, stir for 5-10 hours to completely dissolve it, then weigh 70wt%-80wt% of zinc powder, 8wt%-12wt% of multi-walled carbon nanotube powder and 5wt%-10wt% of tin powder in the solid into a mortar, mix and grind for 20-40 minutes, then add it to the above-mentioned binder solution, and stir continuously for 12-24 hours. When the solid content of manganese dioxide electrode slurry is 16wt%-20wt%, first weigh 8wt%-12wt% of polyvinylidene fluoride (PVDF) powder in the solid, add it to 5-10 ml of N-methylpyrrolidone (NMP) solvent and stir for 5-10 hours to completely dissolve it, then weigh 65wt%-75wt% of manganese dioxide powder and 15wt%-25wt% of conductive carbon black in the solid, mix and grind them in a mortar for 20-40 minutes, then add them to the above binder solution, stir continuously for 12-24 hours, and obtain manganese dioxide electrode slurry after uniform mixing.
5. The preparation method according to claim 2, characterized in that: The specific preparation process of the fiber gel zinc powder negative electrode in step (3) is as follows: the prepared zinc powder slurry is loaded into a slurry barrel, and the motor is started to make the customized copper wire fiber current collector pass through the barrel filled with zinc powder slurry at a uniform speed of 2-6 revolutions per minute, and then pass through a temperature gradient hot blast drying tube, and the drying temperatures of the front, middle and rear sections are 170-190 degrees Celsius, 130-150 degrees Celsius and 90-110 degrees Celsius respectively, and then wind and roll to obtain a fiber zinc powder negative electrode; then, in a vacuum glove box, the obtained fiber zinc powder electrode is soaked in an organic gel precursor solution and irradiated by an ultraviolet light irradiation device for 1-3 minutes, and after in-situ photoinitiated free radical polymerization, it is rolled up to obtain a fiber gel zinc powder negative electrode.
6. The preparation method according to claim 2, characterized in that: The specific preparation process of the fiber manganese dioxide positive electrode in step (4) is as follows: the prepared manganese dioxide electrode slurry is loaded into the slurry barrel, the motor is started to make the customized nickel wire fiber current collector pass through the barrel filled with manganese dioxide slurry at a speed of 2-6 revolutions per minute, and then pass through the temperature gradient hot blast drying tube, and the drying temperatures of the front, middle and rear sections are 130-150 degrees Celsius, 90-110 degrees Celsius and 50-70 degrees Celsius respectively; Then the fiber manganese dioxide positive electrode is obtained by winding and rolling.
7. The preparation method according to claim 2, characterized in that: The specific assembly process of the fiber aqueous zinc ion full battery in step (5) is as follows: first, the fiber manganese dioxide positive electrode is wound around a cellulose diaphragm with a width of 2-4 mm through a diaphragm winding device, and then twisted with the fiber gel zinc powder negative electrode through a twisting device to obtain a fiber zinc ion battery cell with a wound structure, which is then packaged using a commercial FEP tube and injected with a 0.5-2 mol / L bis(trifluoromethanesulfonyl)imide zinc (Zn(TFSI)2) liquid electrolyte, the tabs are drawn out and the two ends of the fiber are sealed with hot melt adhesive to obtain a fiber aqueous zinc ion full battery.
Citation Information
Patent Citations
Aqueous zinc ion battery based on manganese dioxide / graphene and preparation method
CN110729518A
Flexible fibrous knittable lithium ion battery negative electrode as well as preparation and application thereof
CN115172750A
Neutral zinc air fiber battery and preparation method thereof
CN116207410A
Zinc powder and fiber mixtures for electrochemical batteries and cells
US20120052376A1
Electrochemical cell and cell assembly process
US6333127B1